Analysis of callable bonds - Gloneková, Lenka; Radová, Jarmila; Bouček, Karel; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2021)
The aim of this diploma thesis is to analyse the debt market and find the issuance volume of callable bonds. Theoretical part of this diploma thesis is focused on the theoretical foundations of callable bonds, as well as other instruments, such as options, interest rate swaps and swaptions. Practical part contains explanation of Treasury yield curve, spot rate curve and forward rate curve, as well as their relation between each other. Valuation of callable bonds is done by binomial interest rate tree model, using Treasury yield curve and Z-spread obtained from the real market data. Finally, the analysis of volume of bonds is done for the U.S. debt market, with focus on each sector of debt market. Issuance volume of callable bonds is then calculated for years 1996-2020.
Vedoucí práce: Jarmila Radová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: finanční inženýrství [obor dipl. práce]; diplomové práce; master's theses